2023
DOI: 10.1002/mds.29569
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasound Thalamotomy for Tremor in Parkinson's Disease: Outcomes in a Large, Prospective Cohort

Abstract: BackgroundMagnetic resonance guided focused ultrasound (MRgFUS) is United States Food and Drug Administration approved for the treatment of tremor‐dominant Parkinson's disease (TdPD), but only limited studies have been described in practice.ObjectivesTo report the largest prospective experience of unilateral MRgFUS thalamotomy for the treatment of medically refractory TdPD.MethodsClinical outcomes of 48 patients with medically refractory TdPD who underwent MRgFUS thalamotomy were evaluated. Tremor outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Gait disturbances and paraesthesias were the most common side effects [32,40]. Consistent with observations in essential tremor patients [17,41], we also observed taste disturbances and delayed occurrence of involuntary movements, most likely corresponding to "thalamic" dystonia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Gait disturbances and paraesthesias were the most common side effects [32,40]. Consistent with observations in essential tremor patients [17,41], we also observed taste disturbances and delayed occurrence of involuntary movements, most likely corresponding to "thalamic" dystonia.…”
Section: Discussionsupporting
confidence: 90%
“…Bradykinesia and rigidity of the treated side improved initially but this effect faded over time-either because of disease progression or more likely edema regression. Previous studies targeting the VLpv nucleus, reported diminishing effects on rigidity, too [32]. The adjacent anterior (VLa) and posterodorsal part (VLpd) of the ventralolateral nucleus (corresponding to the ventri-oralis anterior (Voa) and posterior (Vop) nucleus in the Schaltenbrand atlas [6]), which receive pallidal projections, are considered to be associated with rigidity [34] and thus might be affected by perilesional edema after VLpv ablation.…”
Section: Discussionmentioning
confidence: 99%
“…7,33,57 VIM-MRgFUS may be an alternative for tremor-dominant older PD patients with asymmetric tremor presentation as it achieves a relevant unilateral tremor reduction confirmed by lower-quality evidence. 25,59 Evidence for long-term efficacy is increasing, but still limited for MRgFUS, 68,69 whereas for DBS long-term efficacy is well established. 31,32 Potential Limitations.…”
Section: Elderly Tremor Patientmentioning
confidence: 99%
“…Furthermore, patients with SDR <0.45 may represent 30-40% of ET patients who could potentially benefit from MRgFUS, especially East Asian patients who tend to have lower SDRs (15)(16)(17). The FDA's SDR cutoff of 0.45 (±0.05) may therefore exclude a significant proportion of patients who could benefit from an effective therapy with a growing number of indications (18).…”
Section: Introductionmentioning
confidence: 99%